2004
DOI: 10.1017/s0265021504003084
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of EMLA and lidocaine iontophoresis for cannulation analgesia

Abstract: Although lidocaine iontophoresis is effective more quickly than the eutectic mixture of local anaesthetic cream, the superior quality of analgesia produced by the eutectic mixture in this study should be borne in mind if these treatments are used electively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The primary outcome, pain, was measured in a variety of ways including: a visual analogue scale (VAS) ( n = 22 studies [ 1 , 14 – 17 , 27 , 30 32 , 35 , 37 , 39 – 41 , 43 , 44 , 46 49 , 51 53 , 56 ]), a numerical rating scale ( n = 6, [ 13 , 29 , 34 , 38 , 50 , 54 ]), Wong Baker Faces ( n = 1, [ 28 ]) and, other ( n = 4 [ 30 , 33 , 36 , 45 ]). Four studies reported that participants had been given pre-medication prior to PVC [ 29 , 42 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome, pain, was measured in a variety of ways including: a visual analogue scale (VAS) ( n = 22 studies [ 1 , 14 – 17 , 27 , 30 32 , 35 , 37 , 39 – 41 , 43 , 44 , 46 49 , 51 53 , 56 ]), a numerical rating scale ( n = 6, [ 13 , 29 , 34 , 38 , 50 , 54 ]), Wong Baker Faces ( n = 1, [ 28 ]) and, other ( n = 4 [ 30 , 33 , 36 , 45 ]). Four studies reported that participants had been given pre-medication prior to PVC [ 29 , 42 , 45 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…[75][76][77][78] There is some evidence that a 15-minute application of lidocaine iontophoresis works as well as an hour-long application of lidocaine/prilocaine cream or the less desirable lidocaine infiltration. [79][80][81][82] The final, needle-free delivery method commonly used is pressurized gas, which creates an ultra-fine stream of medication that penetrates the skin (J-Tip, National Medical Products). For analgesia prior to venous access, the syringe is loaded with buffered lidocaine (preloaded syringes can be purchased), and the device is placed firmly against the skin.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 It has compared favorably with EMLA and injectable lignocaine in randomized trials. 33 Its advantage is that it only takes about 10 to 15 minutes to be effective. Disadvantages are the need for specific equipment and side effects of a burning sensation, erythema or blistering and the fear that small children exhibit toward the device.…”
Section: Iontophoresismentioning
confidence: 99%